2006
DOI: 10.1002/yea.1370
|View full text |Cite
|
Sign up to set email alerts
|

A 5‐hydroxymethyl furfural reducing enzyme encoded by the Saccharomyces cerevisiae ADH6 gene conveys HMF tolerance

Abstract: The fermentation of lignocellulose hydrolysates by Saccharomyces cerevisiae for fuel ethanol production is inhibited by 5-hydroxymethyl furfural (HMF), a furan derivative which is formed during the hydrolysis of lignocellulosic materials. The inhibition can be avoided if the yeast strain used in the fermentation has the ability to reduce HMF to 5-hydroxymethylfurfuryl alcohol. To enable the identification of enzyme(s) responsible for HMF conversion in S. cerevisiae, microarray analyses of two strains with diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
181
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(198 citation statements)
references
References 33 publications
10
181
0
4
Order By: Relevance
“…12,15,29 Researchers stated that, overexpression of the dehydrogenase/reductase genes (ari1, adh7, ald6 and adh6) increased enzyme activities for furfural and/or HMF reduction and simultaneously improved the tolerability of yeast against inhibitors. [12][13][14]30 Quantitative real-time PCR data confirmed the overexpression of tps1 and ari1 in engineered strain SCTADN. As compare with wild strain (SC), SCTADN exhibited significantly higher cell survival under stresses of ethanol, furfural and HMF.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…12,15,29 Researchers stated that, overexpression of the dehydrogenase/reductase genes (ari1, adh7, ald6 and adh6) increased enzyme activities for furfural and/or HMF reduction and simultaneously improved the tolerability of yeast against inhibitors. [12][13][14]30 Quantitative real-time PCR data confirmed the overexpression of tps1 and ari1 in engineered strain SCTADN. As compare with wild strain (SC), SCTADN exhibited significantly higher cell survival under stresses of ethanol, furfural and HMF.…”
Section: Discussionmentioning
confidence: 86%
“…[10][11][12] Many researches demonstrated that overexpression of the aldehyde dehydrogenase/reductase genes (ari1, ald6 and adh6) in S. cerevisiae not only could eliminate the toxicity of aldehydes but also improve tolerability. [12][13][14][15] Trehalose, a non-reducing disaccharide, works as an energy source in yeasts, bacteria, fungi, invertebrates, insects and plants. 16,17 Many research demonstrated that the higher trehalose accumulated in the yeast cell the higher tolerance against various environmental stresses, for instance ethanol stress, 18 heat stress, 19 saline stress, 20 and various other environmental stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, HmfH provides an alternative to the nonspecific dehydrogenases that also perform these upper pathway oxidations in C. basilensis HMF14. Such nonspecific "furanic dehydrogenases" were also observed in P. putida S12, as well as in other microorganisms that cannot utilize furanic aldehydes for growth, probably serving to detoxify furanic aldehydes (31)(32)(33).…”
Section: Discussionmentioning
confidence: 86%
“…Trialkylamine [79] Liquid-solid extraction Activated carbon [80] Ion exchange [38,81] Lignin [82] Microbial treatment Coniochaeta ligniaria [83,84] Trichoderma reesei [33,85] Ureibacillus thermosphaericus [86] a The phenolics [89,90], furan aldehydes [91,92], and aliphatic acids [93,94]. Furthermore, overexpression of a transcription factor, Yap1 [95], and of multidrug-resistance proteins [95] has also generated hyperresistant S. cerevisiae transformants.…”
Section: Strategies To Counteract Inhibition Problemsmentioning
confidence: 99%